2010
DOI: 10.1016/j.bcp.2010.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Small hyaluronan oligosaccharides induce inflammation by engaging both toll-like-4 and CD44 receptors in human chondrocytes

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 34 publications
6
104
1
3
Order By: Relevance
“…25) For instance, oligosaccharides of hyaluronan activated dendritic cells via TLR4 to induce TNF-α 19) and they induced inflammation in chondrocytes through TLR4 and CD44 receptors. 21) These findings support the involvement of TLRs in the macrophage-stimulating activities of AOs.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…25) For instance, oligosaccharides of hyaluronan activated dendritic cells via TLR4 to induce TNF-α 19) and they induced inflammation in chondrocytes through TLR4 and CD44 receptors. 21) These findings support the involvement of TLRs in the macrophage-stimulating activities of AOs.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, a previous report has suggested that hyaluronan oligosaccharides activate dendritic cells via toll-like receptor (TLR) 4 to induce TNF-α, and the activity of hyaluronan oligosaccharides is greater than that of hyaluronan polysaccharides. 19,21) Thus, oligomerization might represent a promising strategy to increase the bioactivities of these polysaccharides. Previous studies on the structure-activity relationships of AOs have demonstrated that the TNF-α-inducing activities of enzymatically depolymerized AOs in RAW264.7 cells vary with the size and composition of the oligomer.…”
Section: Discussionmentioning
confidence: 99%
“…2 shows the chemical structure of the repeating units of HA and its derivatives. The hydrazinloysis reaction done at 72 h (DHA) generated HA within the molecular mass range that is known to generate an inflammatory response and was therefore used for further studies (9,17,29). In this sample (DHA), the ratio of the integration of the NMR peaks for the three methyl protons in the GlcNAc unit and the anomeric protons of the GlcNAc, GlcUA, and glucosamine was calculated to be 1.24 Ϯ 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that AHA exerts its stimulatory effect on proinflammatory cytokine production by interacting with the TLR-4 cell surface receptor. It has been reported that small molecular mass fragments of HA can exert their inflammatory response either through the TLR-4 receptor or the CD44 cell surface receptor (9,12,17). To determine whether AHA also exerts its inflammatory response through the CD44 cell surface receptor, THP-1 macrophages were treated with AHA with or without the CD44 agonist, HA, or antibodies to CD44.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation